Bioactive glass granules versus standard autologous and allogeneic bone grafts: a randomized trial of 49 adult bone tumor patients with a 10-year follow-up - Aro Hannu T; Välimäki Ville-Valtteri; Strandberg Niko; Lankinen Petteri; Löyttyniemi Eliisa; Saunavaara Virva; Seppänen Marko (Medical Journal Sweden AB, 2022)
Background and purpose:
As a synthetic bone void filler, bioactive glasses (BGs) may enhance angiogenesis and osteogenesis. In this randomized trial, we compared the clinical efficacy of BG granules and standard bone grafts in patients undergoing surgery for benign bone tumors.
Patients and methods:
49 recruited patients were randomized to receive BG granules or undergo conventional bone grafting to fill defects following tumor removal. As the standard of care, small-sized defects were filled with autologous graft, and large-sized defects were filled with allogeneic graft. The primary endpoint was treatment success at 1 year, defined by no reoperation, no tumor recurrence, and no device-related adverse events. Secondary endpoints included patient-reported outcomes (Rand-36 and pain scores) and quantitative assessment of blood flow and metabolic activity by means of F-18-fluoride PET/CT imaging. As an off-trial group, 15 children and adolescents (age < 18 years) underwent tumor removal and BG-filling, without randomization.
Results:
At 1-year, 21 of 25 BG-treated patients (risk estimate 0.84, 95% confidence interval [CI] 0.70-0.98) and 20 of 24 patients in the standard of care group (0.83, CI 0.68-0.98) met the criteria for treatment success. The groups had similar Rand-36 scores. In patients with small defects, BG filling was associated with shorter operative time and less postoperative pain at 1 month. In patients with large defects, blood flow was similar, but BG-filled defects showed higher metabolic activity than allograft-filled defects at 1-year. The survey of the postoperative period >= 10 years revealed no BG-related adverse events.
Interpretation:
BG granules had similar overall rates of treatment success compared with autografts and allografts, but large-scale trials are needed for the confirmation of clinical equivalence. The extended metabolic activity confirms the expected cellular responses of osseointegrated BG granules.